Avaliação da qualidade da assistência prestada às mulheres para prevenção e controle do câncer do colo do útero na atenção primária em Sobral-CE - Ramos, Vanessa Mesquita (2014)
Despite ongoing efforts that are being applied in the prevention and control of cervical cancer over the past decades, it remains a major challenge for health in our country. This is because actions require varying degrees of complexity and human resources from different areas of knowledge. The primary health care plays an important role in the various dimensions of care for cancer of the cervix, it has a strategic role to develop actions in planning, implementation and related to the prevention, detection, treatment and rehabilitation of women with cervical cancer monitoring. This research has the main objective to assess the quality of care provided to women for prevention and control of Cervical Cancer in Primary Health Care in Sobral-CE. This is an assessment study with quantitative-qualitative approach from the standpoint of Donabedian that assessed the structure, process and outcomes in 15 basic health units in the town. 15 managers participated in the survey (structure), 14 doctors and 15 nurses (case) and 58 users (result). The quantitative data were processed in Microsoft Office Excel 2007 and underwent qualitative content analysis of the type proposed by Minayo thematic analysis. This study followed the bioethical principles outlined in Resolution No. 466/12 of the National Board of Health and was approved by the Research Ethics Committee under protocol number 245 512. Research into the structure identified that the availability of physical and material resources is suitable for most units, the collection of Pap smear testing is mostly performed by nurses and gynecological consultations by doctors and by nurses. The process analysis revealed that the units do not have mechanisms for identification and registration of active search of women with late examination, the capture of these is dependent on demand for health services, pipes and referrals depend directly on changes found, there is a good interaction entity levels of care, but with deficits in communication, lack of time for professional in-service training as well as facilitating factors such as free access and weekly offering with fixed and restrictive days as a professional accommodation, lack of women to take and delay in results. In the third and final element, the result, we found the main motivator for seeking care by the need for knowledge about their health status examination attributing to the importance of preventing disease, results for the ease in scheduling and attendance units and satisfaction of users regarding access, gratuity, speed and quality of service offered. We conclude that, in general, the identified structure was adequate for most units investigated, the process of working professionals directly involved proved fragile in the face of activities carried out and the result exposed the opinion and satisfaction of users resulting from shares offered. Contact with all these data allowed the evaluation of the factors involved in the provision of care that can support the analysis and planning of actions for women's health and the ripening of NHS services in our country.